Didactic Strategy to Introduce the Concept of Punctual Continuity with Pre-University Students (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2020)
This paper describes a didactic strategy to introduce the concept of continuous function in pre-university students, based on functions defined in pieces. The theoretical-methodological elements that made possible the exploration design fall in the records of semiotic representation, the formation, and definition of concepts and in the didactic functions of the class. As a result of the experimentation, it was found that the didactic strategy favored in the students the identification of the conditions that guarantee the continuity of a function in a point and under this scheme the step to the classical definition.